Mechanochemical synthesis and characterization of nanocrystalline Ni1-xCoxFe2O4 (0 ≤ x ≤ 1) ferrites - Castrillon Arango, Jhon Alejandro (2019)
Magnetic ferrites Ni1-xCoxFe2O4 are synthesized by means of a simple, clean and scalable route consisting of a solid-state reaction induced by high energy ball-milling between metal salts (Lewis'acids) and sodium hydroxide (base). The chemical reaction occurs at room temperature and produces nanocrystalline Ni1-xCoxFe2O4 and soluble byproducts, which are efficiently removed by washing. Thermal treatments at several temperatures are performed to favor the crystallization of the desired phase. The evolution of the system with mechanochemical reaction and heating is followed by X-ray diffraction, Raman spectroscopy, thermal analyses and scanning electron microscopy. The magnetic properties of the obtained ferrites are studied by Mössbauer spectroscopy and vibrating sample magnetometry. The adequate combination of mechanochemical and thermal treatments leads to obtain pure materials with excellent magnetic properties, depending on the composition, the particle size, the cation distribution and the canted spin structure at the surface of the nanoparticles.